2010
DOI: 10.1177/0017896910379366
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a six-month empowerment-based exercise intervention programme in non-physically active adolescent Swedish girls

Abstract: Objective: This study evaluated changes in self-efficacy in non-physically active adolescent girls (13–19 years old) who participated in a six-month, empowerment-based exercise intervention programme (EIP). Design: The study used a pre- and post-test randomized group design and included one pre- and one post-test (at six months) and non-physically active adolescent girls ( N = 110) were assigned to an intervention group ( n = 54) or a comparison group ( n = 56). Setting: Two upper secondary schools and five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(64 citation statements)
references
References 30 publications
3
56
0
5
Order By: Relevance
“…The included studies were of varying study designs, with 42 48,50,53,54,[57][58][59]62,63,[67][68][69]71,[73][74][75][76][77][78][79][80][81]83,84,86,87,89,90,[93][94][95][96][97]98,102,103,[106][107][108][109][110][111][112][113][114][115][116][117][118][119]124 experimental (largely cluster trials) and 34 [40][41][42][43][44][45][46][47]49,51,…”
Section: Studies Included In the Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies were of varying study designs, with 42 48,50,53,54,[57][58][59]62,63,[67][68][69]71,[73][74][75][76][77][78][79][80][81]83,84,86,87,89,90,[93][94][95][96][97]98,102,103,[106][107][108][109][110][111][112][113][114][115][116][117][118][119]124 experimental (largely cluster trials) and 34 [40][41][42][43][44][45][46][47]49,51,…”
Section: Studies Included In the Reviewmentioning
confidence: 99%
“…studies seldom reported means and standard deviations), it was possible to conduct meta-analysis for only a small subset of interventions in this category (n = 13 targeted interventions). The fifty-two studies are therefore synthesised narratively in terms of whether they followed a universal (n = 16 44,45,57,64,[74][75][76][77]86,88,[96][97][98][100][101][102]104,105 ) or a targeted (n = 36 54,56,[58][59][60][61][62][63][65][66][67][68][69][70][71][72][73][78][79][80][81][82][83][84][85]87,[89][90][91][92][93][94][95]99,103,106 ) approach. The results are also summarised in Table 41 (universal-approach studies) and …”
Section: Targeted Interventionsmentioning
confidence: 99%
See 3 more Smart Citations